If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1p + -8p = 3 + -6p Combine like terms: -1p + -8p = -9p -9p = 3 + -6p Solving -9p = 3 + -6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '6p' to each side of the equation. -9p + 6p = 3 + -6p + 6p Combine like terms: -9p + 6p = -3p -3p = 3 + -6p + 6p Combine like terms: -6p + 6p = 0 -3p = 3 + 0 -3p = 3 Divide each side by '-3'. p = -1 Simplifying p = -1
| -32=-2v | | -2a+5=5 | | 6(2x-9)=-102 | | -4n=-n-6 | | 7x^2-6= | | -39x+31=225 | | -12=-x-5x | | 8x+3=9+5x | | 6=14+n | | 3(5+3x)=-3(6-2x) | | 3x+14=x+24 | | -3x+1=-5x+17 | | 6=10-x | | 3(x+3)=(4+x) | | 2x+2x-1=12 | | 4Y+20=8 | | -3x+8=-2x+9 | | 10x-7= | | 2(2+2)*3= | | -3x-10=x-6 | | [a+5]=7 | | 4+4(2-4b)=-52 | | 2(5x+9)=-38+6 | | 3x+1x=28 | | 400w-3w=10450 | | 2Y+8=22 | | (X+2)(X-9)=-24 | | -3x-6=-x-14 | | 1-3n+n=13 | | (X+2)(X-9)=24 | | 4x=-91 | | 60=4(3x+3) |